Reliability of demand-based warm standby systems subject to fault level coverage - Zhai, Q.; Peng, R.; Xing, L.; Yang, J. (Applied stochastic models in business and industry, 2015)
For mission‐critical or safety‐critical systems, redundancy techniques are often applied to satisfy the stringent reliability requirements of the system design. Warm standby sparing is a common redundancy technique, which compromises the high energy consumption of hot standby techniques and the long recovery time of cold standby techniques. This paper considers a more general model for warm standby systems, that is, the demand‐based warm standby system, where each component bears a nominal capacity and the system fails if the total capacity of the working components cannot meet the system demand. Moreover, fault level coverage is considered to model the imperfect coverage effect in the standby system. A multivalued decision diagram based approach is proposed to evaluate the reliability of the demand‐based warm standby system subject to the fault level coverage. Examples are given to illustrate the proposed method. Copyright © 2014 John Wiley & Sons, Ltd.